Molecular Cloning and Bioinformatics Analysis of a New Plasma Membrane Na(+)/H(+) Antiporter Gene from the Halophyte Kosteletzkya virginica - Wang, Hongyan (Hindawi Publishing Corporation, 2014)

(untitled)
A new plasma membrane Na(+)/H(+) antiporter gene (named as KvSOS1) was cloned from the halophyte Kosteletzkya virginica by reverse-transcription-polymerase chain reaction (RT-PCR) and rapid amplification of cDNA ends (RACE) technology, which is a homologue of SOS1 (salt overly sensitive 1). The full-length cDNA is 3850 bp and contains an open reading frame (ORF) encoding a protein of 1147 amino acids with a molecular weight of 127.56 kDa and a theoretical pI of 6.18. Bioinformatics analysis indicated that the deduced protein appears to be a transmembrane protein with 12 transmembrane domains at the N-terminal region and a long hydrophilic tail in cytoplasm at its C-terminal region and shares 72–82% identity at the peptide level with other plant plasma membrane Na(+)/H(+) antiporters.